2003
DOI: 10.2307/3556619
|View full text |Cite
|
Sign up to set email alerts
|

In the Bud? Disk Array Producers as a (Possibly) Emergent Organizational Form

Abstract: Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
172
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(186 citation statements)
references
References 38 publications
6
172
1
2
Order By: Relevance
“…Thus, resource flows across geographic space are not only a function of an organization's physical presence in a given location, but also of that location's prominence in the organization's attention hierarchy. Moreover, since geography not only distributes attention but is also an important element of an organization's identity (Glynn and Abzug 2002;McKendrick et al 2003;Romanelli and Khessina 2005), geographically defined attention patterns are likely to be relatively stable predictors of organizational resource allocation patterns (Bouquet and Birkinshaw 2008). In the context of our theorizing, we propose that the likelihood of philanthropic responses to emergent human needs in a particular geographic location is a function of the amount of attention an organization tends to pay to that location, and that these effects exist above and beyond the predictive effects of an organization's physical presence in that location.…”
Section: Geographic Attention Focus: Places In the Organizational Attmentioning
confidence: 99%
“…Thus, resource flows across geographic space are not only a function of an organization's physical presence in a given location, but also of that location's prominence in the organization's attention hierarchy. Moreover, since geography not only distributes attention but is also an important element of an organization's identity (Glynn and Abzug 2002;McKendrick et al 2003;Romanelli and Khessina 2005), geographically defined attention patterns are likely to be relatively stable predictors of organizational resource allocation patterns (Bouquet and Birkinshaw 2008). In the context of our theorizing, we propose that the likelihood of philanthropic responses to emergent human needs in a particular geographic location is a function of the amount of attention an organization tends to pay to that location, and that these effects exist above and beyond the predictive effects of an organization's physical presence in that location.…”
Section: Geographic Attention Focus: Places In the Organizational Attmentioning
confidence: 99%
“…O estabelecimento de uma forma advém da ampla aceitação das respectivas audiências, na qual a firma está inserida (MCKENDRICK; JAFFEE; CARROLL; KHESSINA, 2003;PERRETTI;NEGRO;LOMI, 2008). Nessa perspectiva, a identidade organizacional é analisada por meio da configuração da identidade, avaliando características específicas da identidadeda firma.A configuração da identidade é relacionada a aspectos relativos tais como localização geográfica, aspectos sociais e organizacionais.…”
Section: Surgimento Daforma Organizacionalunclassified
“…Conforme a metodologia proposta, o processo de institucionalizaçãofoi analisado por meio das categorias: legitimidade social e legitimidade política(McKENDRICK; JAFFEE; CARROLL; KHESSINA, 2003;ALDRICH;RUEF, 2006;PERRETTI;NEGRO;LOMI, 2008;ROSSONI, 2009). Os resultados são sustentados pelas evidências apresentadas no processo de categorização das entrevistas.…”
Section: Identificar Os Recursos Disponíveis (Nicho De Recursos) E Suunclassified
“…Increased organizational density within a sector contributes to overcoming the liability of newness and increasing legitimacy (Carroll and Hannan, 1989;Hannan et al, 1995;McKendrick and Carroll, 2001): "density is a parsimonious indicator of legitimacy that enjoys predictability for a remarkably wide array of organizations" (Deephouse and Suchman, 2008, p. 55). Density alone, however, is not enough to secure legitimacy; the public must have knowledge of the organizations and be able to recognize and categorize them (Hsu and Hannan, 2005;McKendrick et al, 2003;Navis and Glynn, 2010). Prior studies have found that organizations engage in strategies to increase public recognition and gain legitimacy (for example, Suchman, 1995;Scherer et al, 2013;Tornikoski and Newbert, 2007;Zimmerman and Zeitz, 2002).…”
Section: Legitimation Strategiesmentioning
confidence: 99%